(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It Is known That A.Nawai’s epic” Lison ut-tayr " was taught by F.Attor’s Epic “Logic ut-tayr” is a saga influenced and written in response to it. In both works, the guardians were expressed through figurative images. In the epics, we focused on the two nations of the East, two mentalities, two literature and similar and different aspects of thought, the spiritual unity of the two great creators, the evolution of comparative studies.